Unusual phenolic compounds contribute to ecophysiological performance in the purple‐colored green alga Zygogonium ericetorum (Zygnematophyceae, Streptophyta) from a high‐alpine habitat. Issue 4 (23rd May 2013) - Aigner, Siegfried; Remias, Daniel; Karsten, Ulf; Holzinger, Andreas; Bassi, R.
<x xml:space="preserve">Abstract</x> The filamentous green alga Zygogonium ericetorum (Zygnematophyceae, Streptophyta) was collected in a high‐alpine rivulet in Tyrol, Austria. Two different morphotypes of this alga were found: a purple morph with a visible purple vacuolar content and a green morph lacking this coloration. These morphotypes were compared with respect to their secondary metabolites, ultrastructure, and ecophysiological properties. Colorimetric tests with aqueous extracts of the purple morph indicated the presence of soluble compounds such as phenolics and hydrolyzable tannins. High‐performance liquid chromatography‐screening showed that Z. ericetorum contained several large phenolic peaks with absorption maxima at 280 nm and sometimes with minor maxima at 380 nm. Such compounds are uncommon for freshwater green microalgae, and could contribute to protect the organism against increased UV and visible (VIS) irradiation. The purple Z. ericetorum contained larger amounts (per dry weight) of the putative phenolic substances than the green morph; exposure to irradiation may be a key factor for accumulation of these phenolic compounds. Transmission electron microscopy of the purple morph showed massive vacuolization with homogenous medium electron‐dense content in the cell periphery, which possibly contains the secondary compounds. In contrast, the green morph had smaller, electron‐translucent vacuoles. The ecophysiological data on photosynthesis and desiccation tolerance indicated that increasing photon fluence densities led to much higher relative electron transport rates (rETR) in the purple than in the green morph. These data suggest that the secondary metabolites in the purple morph are important for light acclimation in high‐alpine habitats. However, the green morph recovered better after 4 d of rehydration following desiccation stress.